A prospective evaluation of efficacy and safety of topical bromfenac 0.09% over topical flurbiprofen 0.03% after cataract surgery - Hebbar, Sahana K.; P., Deepak; G. K., Nalini; C. V., Kavitha; G. N., Sahana; Nagaral, Jayashree V. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Different medications are used to reduce pain and inflammation after cataract surgery. Hence this study was taken up to compare the efficacy and safety of topical bromfenac 0.09% over topical flurbiprofen 0.03% in reducing anterior chamber inflammation and pain after cataract surgery. Methods: Total of 100 patients who underwent uneventful cataract surgery with posterior chamber intra ocular lens (IOL) implantation were randomly allocated to receive bromfenac 0.09% and flurbiprofen 0.03% topically from first post-operative day onwards for 6 weeks. Assessment of anterior chamber inflammation and pain was done by slit lamp and visual analogue scale respectively on each follow up days. Analysis was done by unpaired t test and Fischer’s exact test. Results: The response to treatment was earlier in bromfenac group for all the inflammatory changes (significant difference was found on day 7, p<0.05) except for corneal edema where both the groups showed similar response. On 7th day after surgery, 72% patients in flurbiprofen group and 12% in bromfenac group had pain (score1), while on the 14th day none in the bromfenac group complained of pain whereas 4% in flurbiprofen group still had pain. Both the drugs were safe and no clinically serious adverse effects were observed in either of the groups. Conclusions: This study showed both the medications, topical bromfenac 0.09% and topical flurbiprofen 0.03% effective and safe in reducing pain and anterior chamber inflammation after cataract surgery but the response was earlier with bromfenac 0.09%.